National Lampoon's Adam and Eve - Kanew, Jeff.; Cameron, Douglas; Emmanuelle Chriqui; Brianna Brown; Chad Lindberg; Jed Bernard (New Line Home Video, 2004)
Adam and Eve has an interesting premise with a lot of potential as a thoughtful, adult movie. Disheveled musician and college student Adam (Cameron Douglas, son of Michael Douglas) goes out of his way to meet the beautiful Eve (Emmanuelle Chriqui) on campus. In no time, the two are in love. Everything goes swimmingly except in the bedroom, where Eve asserts her right to remain a virgin until she's ready. Adam--though deferential--takes her requirement personally and demands to know what "ready" means. The pair go on like this for months, with Adam remaining true to his passion for Eve, despite howls of protest from his degenerate housemates (among them Jake Hoffman, son of Dustin Hoffman). Eve takes flak, too, from some of her own roomies, yet for awhile it appears Adam and Eve's story will include other young women inspired by Eve's insistence on respect behind closed doors. Unfortunately, writer-director Jeff Kanew (Revenge of the Nerds) elects not to go down that path and nearly derails the movie with inconsequential gross-out scenes at Adam's house. But the material dedicated to Adam and Eve's challenging relationship is discerning.
Languages: English, Turkish Subtitle: Turkish
Keywords: Comedy